2012
DOI: 10.1667/rr2862.1
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function in Rats is Impaired by Low (20 cGy) Doses of 1 GeV/u56Fe Particles

Abstract: Exposure to galactic cosmic radiation is a potential health risk in long-term space travel and represents a significant risk to the central nervous system. The most harmful component of galactic cosmic radiation is the HZE [high mass, highly charged (Z), high energy] particles, e.g., (56)Fe particle. In previous ground-based experiments, exposure to doses of HZE-particle radiation that an astronaut will receive on a deep space mission (i.e., ∼20 cGy) resulted in pronounced deficits in hippocampus-dependent lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 24 publications
5
67
0
Order By: Relevance
“…The most commonly employed tests include the Morris water maze and Barnes maze , novel object recognition, object in place recognition, (Casadesus et al 2004;Kumar et al 2013;Shukitt-Hale et al 2000;Tseng et al 2013), and contextual fear conditioning for hippocampus-dependent memory (especially spatial memory) but with strong associations with the cortex as well. Cognitive behaviors more closely associated with the frontal cortex include operant conditioning Rice et al 2009), attentional set shifting Lonart et al 2012), and psychomotor vigilance tests (Heinz et al 2008;Davis et al 2014). Anxiety and fear are commonly assessed with open field tests and elevated plus or zero mazes (Kumar et al 2013).…”
Section: Behavioral Effects a Overall Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly employed tests include the Morris water maze and Barnes maze , novel object recognition, object in place recognition, (Casadesus et al 2004;Kumar et al 2013;Shukitt-Hale et al 2000;Tseng et al 2013), and contextual fear conditioning for hippocampus-dependent memory (especially spatial memory) but with strong associations with the cortex as well. Cognitive behaviors more closely associated with the frontal cortex include operant conditioning Rice et al 2009), attentional set shifting Lonart et al 2012), and psychomotor vigilance tests (Heinz et al 2008;Davis et al 2014). Anxiety and fear are commonly assessed with open field tests and elevated plus or zero mazes (Kumar et al 2013).…”
Section: Behavioral Effects a Overall Observationsmentioning
confidence: 99%
“…Because of cross-species differences between humans and rodents, the determination of clinical significance for CNS health risks remains an important problem, especially if based on studies in rodents alone. This important issue is compounded for CNS cognitive risks which are known to originate in the frontal cortex, which is highly under developed in rodents compared to humans although rodents do provide some indication of cognitive risks related in the frontal cortex Lonart et al 2012). ...…”
Section: Rationalementioning
confidence: 99%
“…In part by efforts designed to minimize the adverse and unintended side effects of radiotherapy, the use of protons for clinical radiotherapy is rapidly expanding. Outside of the clinical setting, new research in rodents have identified similar adverse cognitive effects resulting from exposure to charged particles typical of the space radiation environment (Britten et al 2012; Lonart et al 2012; Tseng et al 2013). Thus, whether at lower or higher dosing paradigms, exposure of the CNS is associated with an increased risk of developing acute and longer-term cognitive decrements (Greene-Schloesser et al 2012; Lonart et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Outside of the clinical setting, new research in rodents have identified similar adverse cognitive effects resulting from exposure to charged particles typical of the space radiation environment (Britten et al 2012; Lonart et al 2012; Tseng et al 2013). Thus, whether at lower or higher dosing paradigms, exposure of the CNS is associated with an increased risk of developing acute and longer-term cognitive decrements (Greene-Schloesser et al 2012; Lonart et al 2012). The foregoing has become an increasing concern for those exposed under a variety of scenarios, not only due to the increasing numbers of cancer survivors, but also due to the conspicuous lack of any satisfactory long-term solutions for this serious side effect of radiation exposure to the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such publications include studies suggesting that the induction of Alzheimer’s disease may be a space radiation risk (42) and attention deficits may arise following exposure to low doses of space radiation (43). Many other publications have also indicated that there are major CNS space radiation risks [e.g., (4452)]. Radiation exposure to γ-rays (53) or 56 Fe ions (5457) is also known to have adverse effects on CNS and neurobehavior of irradiated animals, including reduced performance in motor tasks and deficits in spatial learning and memory.…”
Section: Introductionmentioning
confidence: 99%